New method of producing tailored blanks with constant thickness. (2017) - Rosochowski, Andrzej; Olejnik, Lech
Abstract: The concept of weight-saving in automotive manufacture by using tailored blanks is well established. The methods used to produce extra strength in particular areas of the blank can be based either on increasing material thickness in those areas or keeping the thickness constant but varying the material properties. Typically the first option is used by welding blank patches of different thickness. From the view point of forming blanks into sheet metal products uniform thickness is less problematic and it can be achieved by welding different materials of the same thickness or localised heat treatment. However, these approaches have major limitations: welding introduces discontinuity in material structure and properties while selective heat treatment is difficult to control. A new, original method presented here is based on a local shear deformation of the blank material. The particular process used is incremental equal channel angular pressing. The proposed approach is simulated using finite element modelling and then experimentally verified by producing a constant thickness pure aluminium strip with varying hardness. A discussion of different variants of this approach indicates its potential.